HUBUNGAN PEMBERIAN MP-ASI DAN USIA PERTAMA PEMBERIAN MP-ASI DENGAN KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN DI DESA LEYANGAN KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Virginia, Any; Maryanto, Sugeng; Anugrah, Riva Mustika (JURNAL GIZI DAN KESEHATAN, 2020)
Background: Stunting is a chronic malnutrition problem caused by low nutrition intake. Some of the causes of stunting is inappropriate complementary feeding and inappropriatefirst age for complementary feeding. Objective: The study to aims correlation between complementary feeding and first complementary feeding time with stunting in children of 6-24 months Method: The cross-sectional approach was conducted to this study. The 78 respondents were taken by proportional random sampling.Data taken by was an interview with questionnaires and anthropometric measurements using length board. Univariate data analysis by frequency distribution and bivariate data analysis by chi-square and risk estimate Result:The frequency of complementary feeding, the texture of complementary feeding, the amount of complementary feeding and the first age of giving complementary feeding appropriate eachwere60.3%, 65.4%, 33.3%, and 53.8%There was acorrelation between the frequency of complementary feeding (p-value=0.002;OR=4.531), the texture of complementary feeding (p-value=0.015; OR=3.304), amount of complementary feeding (p-value=0.020;OR=3.6), the first age for complementary feeding (p-value=0.002;OR=4,583) with stunting at the age of 6-24 months in Leyangan Village, East Ungaran District, Semarang Regency Conclution: There was a significant correlation between complementary feeding and first complementary feeding time with stuntingin childrenof 6-24 months in Leyangan Village, East Ungaran District, Semarang Regency Abstrak : Latar Belakang: Stunting merupakan masalah kurang gizi kronis yang disebabkan asupan gizi yang rendah. Beberapa penyebab stunting adalah pemberian MP ASI dan usia pertama pemberian MP-ASI yang tidak sesuai. Tujuan: Untuk mengetahui hubungan pemberian MP-ASI dan usia pertama pemberian MP-ASI dengan kejadian stunting pada anak usia 6-24 bulan Metode Penelitian: Desain penelitian ini menggunakan pendekatan cross sectional. Sampel pada penelitian ini ditentukan dengan proportional random sampling sejumlah 78 responden. Data yang diambil adalah wawancara dengan kuisioner dan pengukuran antropometri menggunakan length board. Analisis data univariat menggunakan distribusi frekuensi dan analisis data bivariat menggunakan uji chi square dan risk estimate. Hasil : Frekuensi pemberian MP ASI, tekstur MP ASI yang diberikan, jumlah pemberian MP ASI dan usia pertama pemberian MP ASI sesuai masing-masing 60,3%, 65,4%, 33,3% dan 53,8%.Terdapat hubungan frekuensi pemberian MP ASI (p value=0,002;OR=4,531), tekstur MP-ASI yang diberikan (p value=0,015; OR=3,304), jumlah pemberian MPASI (p value=0,020;OR=3,6), usia pertama pemberian MP-ASI (p value=0,002;OR=4,583) dengan stunting pada usia 6-24 bulan di Desa Leyangan Kecamatan Ungaran Timur Kabupaten Semarang. Simpulan : Terdapat hubungan pemberian MP-ASI dan usia pertama pemberian MP-ASI dengan kejadian stunting pada anak usia 6-24 bulan di Desa Leyangan Kecamatan Ungaran Timur Kabupaten Semarang